Islamic Radicalism Online: The Moluccan Mission of the Laskar Jihad in Cyberspace - Bräuchler, Birgit (The Australian journal of anthropology, 2004)
The Internet has become an important instrument for the information politics of radical Muslim groups. This paper focuses on one of the Islamist groups that have emerged in Indonesia recently—the Communication Forum of the Followers of the Sunnah and the Community of the Prophet (FKAWJ). The FKAWJ sent its fighters, the so-called Laskar Jihad or Jihad troop/fighters, to Ambon in April 2000 to help their Muslim brothers against the ‘Christian attackers’ in the Moluccan conflict—a conflict that was also extended into cyberspace by several actors. Describing the Internet presence of the Laskar Jihad, I give an example of how Islamism is being transferred into cyberspace. The position of the FKAWJ concerning the situation in the Moluccas is outlined as well as other (online) strategies used. Through these strategies the cyber actors create an image and construct an identity that is congruent with their offline philosophy but extends its reach. It is evident that the online level is highly interconnected with the offline level. When analysing contemporary Islamism it is essential to take both levels into account.